Farewell to Fiestas and Saints? Changing Catholic Practices in Contemporary Rural Oaxaca - Toomas Gross (Journal of Ethnology and Folkloristics)
This article discusses recent changes in Catholic festivities, especially the system of fiestas in rural Mexico. The ethnographic focus of the discussion is on indigenous Zapotec communities of the State of Oaxaca. Collective religious practices in Mexican villages contribute to social cohesion. Fiestas commemorating patron saints of the villages play a particularly important role in (re)constructing communal identity and the feeling of collective belongingness. Various global processes like secularisation, integration of local economies into the capitalist market system, increasing out-migration from villages, and the rise of Protestantism have undermined the position of the Catholic Church in the region. The article scrutinises the changing organisation and role of fiestas in the communities, concluding that the impact of secularisation, migration and Protestantism in particular is not simple and always negative – these changes can actually invigorate certain dimensions of the fiestas.